2021
DOI: 10.1016/j.psj.2021.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Response of lymphatic tissues to natural feed additives, curcumin (Curcuma longa) and black cumin seeds (Nigella sativa), in broilers against Pasteurella multocida

Abstract: The antibiotic residues and pathogenic resistance against the drug are very common in poultry because of antibiotics used in their feed. It is necessary to use natural feed additives as effective alternatives instead of a synthetic antibiotic. This study aimed to investigate the immune response of Nigella sativa and Curcuma longa in broilers under biological stress against Pasteurella multocida . The total 100, one-day-old chicks were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Equivalent to the carcass yield, turmeric treatments did not affect liver percentage in KUB chickens (p>0.05). A similar study also revealed that herbal supplementation did not alter liver percentage in kampung chickens [11]. This condition indicates that turmeric supplementation is safe and has no adverse effect since there is no alteration in the liver tissue of KUB chickens.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Equivalent to the carcass yield, turmeric treatments did not affect liver percentage in KUB chickens (p>0.05). A similar study also revealed that herbal supplementation did not alter liver percentage in kampung chickens [11]. This condition indicates that turmeric supplementation is safe and has no adverse effect since there is no alteration in the liver tissue of KUB chickens.…”
Section: Resultsmentioning
confidence: 52%
“…The parameter observed included carcass and its cut parts, liver, and abdominal fat percentages. Each parameter was calculated as the percentage of live body weight [5,11].…”
Section: Methodsmentioning
confidence: 99%
“…Seventeen studies were eligible and relevant to the intervention (i.e., NSS) and the prespecified outcomes in healthy animals [ [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. All 17 studies were assessed for internal validity (risk of bias (RoB) assessment).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported that NSS significantly increased serum titers of anti-NDV antibodies [ 31 , 33 , 34 , 39 ]. Conversely, four studies reported that NSS failed to induce significant changes in serum anti-NDV titers [ 25 , 29 , 30 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation